Evaluation of Organizational Adaptation Mechanisms to Socio-Ecological Change: A Case Study in an Agrarian Community - Bahar, Nur Anita (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This study aims to evaluate organizational adaptation mechanisms in agrarian communities facing socio-ecological change, with a focus on the relative influence of structural and cultural factors on adaptive capacity. Subjects and Methods: A quantitative cross-sectional survey was conducted among members and leaders of agrarian organizations in South Sulawesi, Indonesia. Data were collected using structured questionnaires and analyzed through descriptive statistics, correlation analysis, and multiple regression, with reliability and validity testing to ensure measurement robustness. Results: The findings indicate that both structural mechanisms, including policy alignment, organizational restructuring, and network collaboration, and cultural mechanisms, such as local knowledge integration, social learning, and shared norms, significantly influence adaptive capacity. However, cultural mechanisms demonstrate a stronger effect, highlighting the importance of socially embedded practices in shaping organizational responses. The integration of structural and cultural dimensions further enhances the explanatory power of the model, indicating a synergistic relationship between institutional arrangements and social processes. Conclusions: Organizational adaptation is a multidimensional and context-dependent process, where cultural dynamics play a central role, supported by structural conditions, in strengthening resilience within agrarian communities.